Modal identification methods in cable-stayed bridges case study: Puente Rayitos de Sol - León Deza, Julio Alfredo (2022)
Accurate estimation of modal parameters of cable-stayed bridges plays a key role in evaluating the safety of these structures under dynamic loads such as traffic, wind and earthquakes. Furthermore, the difficulty in exciting this type of structure makes ambient vibration measurements a significant source of information to validate the developed full three-dimensional finite element models that are used to evaluate the dynamic response of this type of bridges. In this work, the Rayitos de Sol cable-stayed bridge was selected as a case study. To evaluate the modal parameters of the bridge, environmental vibration data were collected from strategic points on the platform. Using data recorded in the field, a series of system identification methods were carried out and then compared in the time and frequency domain. The collected data were analyzed based on only-output identification methods: peak selection, frequency domain decomposition, stochastic subspace identification, random decrement, and Ibrahim time domain identification. The purpose of performing different analyzes is to examine the effectiveness and limits of applicability of these techniques to address the specific challenges involved in stage-wise bridge modal identification. To complement the environmental vibration data analysis, the validated finite element model of the bridge was subjected to artificial environmental excitations for a comprehensive comparison of identification methods. In the development of the numerical model, considering the effective stiffness of the reinforced concrete elements, as well as modeling the correct boundary conditions in the expansion joints, were the main factors to achieve a good correlation with the measured modal parameters.